Perinatal effects of scorpion venoms: maternal and offspring development - Ana Leticia Coronado Dorce; Adriana do Nascimento Martins; Valquiria Abrão Coronado Dorce; Ana Leonor Abrahão Nencioni (Journal of Venomous Animals and Toxins including Tropical Diseases, 2017)
Abstract Scorpion envenomation is a public health problem, especially in tropical and subtropical countries. Considering the high incidence of scorpionism in some areas, pregnant women and nursing mothers may be possible victims. Scorpion stings alter the release of neurotransmitters and some cytokines. These mediators act as organizers and programmers in the adequate formation of the nerves, and non-physiological concentrations of them during the brain organization originate disorders and diseases that can appear later in the life of the individual. Despite the importance of this subject, there are only a few studies showing the effects of scorpion venom on maternal reproductive development, in the morphology and physical and behavioral development of offspring. The present review article summarizes the major findings on this issue. Biochemical changes in the blood – such as hyperglycemia, increase on the level of sodium and on the creatinine concentration – are observed after scorpion sting in humans and experimental animals. Some studies in the literature demonstrate that the scorpion venom affects the maternal reproductive development in humans and in experimental animals, increasing the frequency and amplitude of uterine contraction and the number of resorptions. The venom can also lead to some alterations in the embryonic or fetal development increasing the total weight of fetuses and of some organs. Moreover, it affects the general activity and locomotion during childhood and adulthood, and the anxiety level in adult females and males. It also alters the number of hippocampal neurons and interferes in the level of some cytokines. Altogether, it is evident that the venom, when administered during the pregnancy or lactation, affects the development of the offspring. Studies are being conducted to determine the actual participation of the venom in the development of the offspring, and to what extent they are detrimental to animal development.